Community surveys and risk factor analysis of human alveolar and cystic echinococcosis in Ningxia Hui autonomous region, China - Yu Rong Yang; Tao Sun; Zhengzhi Li; Jianzhong Zhang; Jing Teng; Xongzhou Liu; Ruiqi Liu; Rui Zhao; Malcolm K Jones; Yunhai Wang; Hao Wen; Xiaohui Feng; et al. (The World Health Organization, 2006)
OBJECTIVE: To determine the true community prevalence of human cystic (CE) and alveolar (AE) echinococcosis (hydatid disease) in a highly endemic region in Ningxia Hui, China, by detecting asymptomatic cases. METHODS: Using hospital records and "AE-risk" landscape patterns we selected study communities predicted to be at risk of human echinococcosis in Guyuan, Longde and Xiji counties. We conducted community surveys of 4773 individuals from 26 villages in 2002 and 2003 using questionnaire analysis, ultrasound examination and serology. FINDINGS: Ultrasound and serology showed a range of prevalences for AE (0-8.1%; mean 2%) and CE (0-7.4%; mean 1.6%), with the highest prevalence in Xiji (2% for CE, 2.5% for AE). There were significant differences in the prevalence of CE, AE and total echinococcosis between the three counties and villages (with multiple degrees of freedom). While hospital records showed 96% of echinococcosis cases attributable to CE, our survey showed a higher prevalence of human AE (56%) compared to CE (44%). Questionnaire analysis revealed that key risk factors for infection were age and dog ownership for both CE and AE, and Hui ethnicity and being female for AE. Drinking well-water decreased the risk for both AE and CE. CONCLUSION: Echinococcosis continues to be a severe public health problem in this part of China because of unhygienic practices/habits and poor knowledge among the communities regarding this disease.